DISTURBANCE INDEX FOR FOREST CLASS BASED ON PATCH METRICS OF DAPOLI TALUKA, RATNAGIRI (International Journal of Food and Nutritional Sciences, 2022)
Disturbance- artificial or natural- is an inherent process of a landscape. Land use pattern and disturbances are closely interlinked in biotic prone zone. Disturbances have direct impact on structural and functional patterns of landscape viz. species richness, landscape/ habitat diversity, energy and nutrient flow etc. ecological disturbance, an event or force, of nonbiological or biological origin, that brings about mortality to organisms and changes in their spatial patterning in the ecosystems they inhabit. Disturbance plays a significant role in shaping the structure of individual populations and the character of whole ecosystems.Minor disturbances include localized wind events, droughts, floods, small wildland fires, and disease outbreaks in plant and animal populations. In contrast, major disturbances include large-scale wind events (such as tropical cyclones), volcanic eruptions, tsunamis, intense forest fires, epidemics, ocean temperature changes stemming from El Niño events or other climate phenomena, and pollution and land-use conversion caused by humans. The notion of ecological disturbance has deep historical roots in ecological thinking; the first conceptual disturbance-related model in modern ecology was ecological succession, an idea emphasizing the progressive changes in ecosystem structure that follow a disturbance.